Stacked 1/3 Tubular Plates for Fixation of Pediatric Forearm Fractures: A Biomechanical Study - Cooper, Benjamin; Wendling, Alexander; Isaacs-Pullins, Sharon; White, Joel; Hollenbeck, Steven (Kansas Journal of Medicine, 2022)
Introduction. Among operatively treated pediatric forearm fractures, many different fixation constructs are described. The goal of this study is to define the biomechanical properties of a double stacked 1/3 tubular plate construct used by the senior author for some fractures and to review available literature regarding the use of stacked plates.Methods. Biomechanical testing was performed by 4-point bending of 3 different plate constructs: 1/3 tubular plate, stacked 1/3 tubular plates, and 2.7 mm LC-DCP plate. Five test specimens were evaluated for each of the three plate constructs.  From stress-strain curves, flexural stiffness (N/mm), force to cause plastic deformation (N), and force to cause 10º bend (N) were calculated and compared using standard t-test statistics.Results. Key outcome parameter means (± SD) for the three plate constructs (1/3 tubular plate, stacked 1/3 tubular plates, and 2.7 mm LC-DCP plate) are reported respectively as follows: flexural stiffness (55.4 ± 3.5 N/mm, 131.7 ± 3.5 N/mm, 113.3 ± 12.1 N/mm), force to cause plastic deformation (113.6 ± 11.0 N, 242.1 ± 13.0 N, 192.2 ± 17.9 N), and force to cause a 10º bend (140.0 ± 8.4 N, 299.4 ± 14.1 N, 265.5 ± 21.2 N).  Mean values of all three measures were significantly larger for the stacked 1/3 tubular plates than for the other plate constructs.Conclusions. The stacked 1/3 tubular plate construct was biomechanically superior to the other plate constructs. Stacked plating significantly improves stiffness of the fracture fixation construct supporting use of this technique in selected trauma cases.